Evaluation of natural pigment extracted from dragon fruit (Hylocereus Polyrhizus) peels / Kavirajaa Pandian Sambasevam …[et al.] - Sambasevam, Kavirajaa Pandian; Yunos, Norfateha; Mohd Rashid, Hasratul Nadiah; Baharin, Siti Nor Atika; Suhaimi, Nur Farahin; Raaov, Muggundha; Shahabuddin, Syed (Universiti Teknologi MARA Shah Alam, 2020)
Dragon fruit (Hylocereus polyrhizus), which comes from the family of Cactaceae, is one of the tropical fruits in Malaysia. The peels of red dragon fruit consist of a high content of betacyanin pigment, which responsible for the red-violet colour even though the peel always regarded as a waste. This study aims to evaluate the natural pigment extract from dragon fruits peels using water as a solvent in the extraction method. The colour pigment content was determined based on the absorbance and characterised using Ultraviolet-visible (UV-Vis) at 535 nm and Fourier Transform Infrared (FTIR) spectrometer, respectively. Several extraction parameters were studied and optimised to obtain the optimum condition of the extraction process, including extraction time, extraction temperature, pH, and pigment extract stability towards the light. Results analysis from the pigment extract showed that the optimum conditions were achieved at 4 hours, 25 °C and pH 5 for extraction time, temperature, and pH, respectively. However, the sample pigment extract shows decreased in total betacyanin content over time as it exposed to light but still stable compared to control. In conclusion, the natural pigment extracted from dragon fruit peels using water as a solvent in the extraction method has a high potential to be used as a natural colourant. Moreover, the use of natural resources extracted from peels could be successfully employed as an effective, eco-friendly alternative cleaner and provide a new opportunity to replace the synthetic colourant.